HUBUNGAN PROFESIONALITAS PRAMUWISATA DENGAN TINGKAT KEPUASAN WISATAWAN DI OBJEK WISATA DANAU GUNUNG TUJUH KABUPATEN KERINCI - Dwi Pratiwi Wulandari (Ensiklopedia of Journal, 2020)
Tour guide profesionality in guiding tourist is the main key of tourist satisfaction. Tourist satisfaction is comparison pra-buying expectation a tour package with services received. If quality of services is so far from expectation, tourist isn’t satisfied, if quality of services is same with expectation, tourist will be satisfied, if quality of service more than expectation, tourist will be so satisfied. This research purpouse to know how the correlation of tour guide profesionality with tourist satisfaction of Danau Gunung Gunung Tujuh Kabupaten Kerinci. Kind of this research is kuantitatif correlative with cross sectional method, dependent and independent variable become research object. The sampling of this research are 60 tourist. Taking sampling doing by purposive sampling technic. To see how the correlation of each variable using statistic test that is chi-square. Based on the result of statistic test of tour guide profesionality variable, obtainable 43 respondent (71,7%) said that there is tour guide profesionality, 18 respondent (18,3%) said that less tour guide profesionality and 6 respondent (10,0%) said that so there tour guide profesionality. The statistic test result of tourist satisfaction variable, obtainable 34 respondent (5,67%) said saitisfied with service of tour guide, 15 respondent (25,0%) said very satisfied with tour guide profesionality and 11 respondent (18,3%) said not satisfied with tour guide profesionality. From statistic test result of chi-square obtainable p value=0,001. So, we can conclude that there is correlation between tour guide profesionality with tourist satisfaction. It mean that more high the level of tour guide profesionality, so more high the degree of tourist satisfaction. Based on the conclution of research, it is suggested the tour guide organizing themself in a tour guide association, so that tour guide can know right, obligation, and code of conduct profesion, and have a training to increase quality of tourist service.